2017
DOI: 10.18632/oncotarget.21831
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibitors, t-AUCB, regulated microRNA-1 and its target genes in myocardial infarction mice

Abstract: PurposeSoluble epoxide hydrolase inhibitors (sEHIs) had been demonstrated to produce cardioprotective effects against ischemia-induced lethal arrhythmias, but the exact mechanisms remain unknown. The present study was designed to investigate whether the beneficial effects of sEHIs are related to regulation of microRNA-1, which was a proarrhythmic factor in the ischemic heart.MethodsA mousemyocardial infarction (MI) model was established by ligating the coronary artery. sEHI t-AUCB (0.2, 1, 5 mg/L in drinking-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…MiR-1 is a muscle-specific miR reported to be tightly associated with CVD. Regarding I/R injury, miR-1 was found to be down-regulated in response to myocardial I/R injury in the heart tissue of rats [48,49] and mice [50], as well as in cardiac-derived H9c2 cells [48] and neonatal cardiac myocytes [51] exposed to hypoxia/reoxygenation (H/R). The level of miR-1 down-regulation was increased with prolonged time of MI in rats, and also with prolonged time of post-hypoxic reoxygenation in H9c2 cells [48].…”
Section: Role Of Mir-1 In Cardiac I/r Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-1 is a muscle-specific miR reported to be tightly associated with CVD. Regarding I/R injury, miR-1 was found to be down-regulated in response to myocardial I/R injury in the heart tissue of rats [48,49] and mice [50], as well as in cardiac-derived H9c2 cells [48] and neonatal cardiac myocytes [51] exposed to hypoxia/reoxygenation (H/R). The level of miR-1 down-regulation was increased with prolonged time of MI in rats, and also with prolonged time of post-hypoxic reoxygenation in H9c2 cells [48].…”
Section: Role Of Mir-1 In Cardiac I/r Injurymentioning
confidence: 99%
“…↓miR-1 in heart tissue in response to I/R in rats, mice, and infarcted human hearts [48][49][50]52,53] ↓miR-1 in H9c2 cells and neonatal cardiac myocytes in response to H/R [48,51] ↑miR-1 in remote myocardium compared to infarcted zone or healthy hearts in infarcted human hearts [54] ↑levels of circulating miR-1 after AMI in pigs and humans [58,59] miR-1 overexpression exacerbated cardiac I/R injury in transgenic mice [55] miR-1 inhibition protects against I/R (H/R) injury in rats, mice, and H9c2 cells [48,55,56] miR-21…”
Section: Type Of Cvd Mir Findings Referencementioning
confidence: 99%
“…Abnormal upregulation of miR-1 suppresses the expression of genes related to the potassium voltage-gated channel subfamily J member 2/Inwardly rectifying K channel 2.1 and the gap junction protein alpha 1/connexin 43 pathway which may then induce arrhythmia by interfering with the K + current during repolarization (Gui et al, 2017).…”
Section: Arrhythmiamentioning
confidence: 99%
“…Currently, it is believed that myocardial ischemia can activate the β-adrenoceptor (βAR)/cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signal pathway, following activated PKA transfers to the nucleus and phosphorylates cAMPresponsive element binding protein CREB. Activated CREB promotes the transcription of miR-1 and other miRNAs (Gui et al, 2017;Shi and Yang, 2016).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Therefore, miR-133 could be a new target for treating ischemic arrhythmias. We previously demonstrated that sEHIs might reduce the incidence of ischemic arrhythmias by suppressing miR-1 in cardiomyocytes [ 18 , 19 ]. As miR-1 and miR-133 are clustered on the same chromosome loci and transcribed together in a tissue-specific manner [ 20 ], we speculated that miR-133 might also contribute to the anti-arrhythmic action of sEHIs.…”
Section: Introductionmentioning
confidence: 99%